Dual Roles of Quercetin in Platelets: Phosphoinositide-3-Kinase and MAP Kinases Inhibition, and cAMP-Dependent Vasodilator-Stimulated Phosphoprotein Stimulation - Oh, Won Jun (Hindawi Publishing Corporation, 2012)
Background. Progressive diseases including cancer, metabolic, and cardiovascular disorders are marked by platelet activation and chronic inflammation. Studies suggest that dietary flavonoids such as quercetin possess antioxidant, anti-inflammatory, and antiplatelet properties, which could prevent various chronic diseases including atherosclerosis and thrombosis. However, the mechanism and the signaling pathway that links quercetin's antiplatelet activity with its anti-inflammatory property is limited and thus further exploration is required. The aim of this paper was to examine the link between antiplatelet and anti-inflammatory roles of quercetin in agonist-induced platelet activation. Methods. Quercetin effects on agonist-activated platelet-aggregation, granule-secretion, [Ca(2+)](i), and glycoprotein-IIb/IIIa activation were examined. Its effects on PI3K/Akt, VASP, and MAPK phosphorylations were also studied on collaged-activated platelets. Results. Quercetin dose dependently suppressed collagen, thrombin, or ADP-induced platelet aggregation. It significantly inhibited collagen-induced ATP release, P-selectin expression, [Ca(2+)](i) mobilization, integrin-α (IIb) β (3) activation, and augmented cAMP and VASP levels. Moreover, quercetin attenuated PI3K, Akt, ERK2, JNK1, and p38 MAPK activations, which were supported by platelet-aggregation inhibition with the respective kinase inhibitors. Conclusion. Quercetin-mediated antiplatelet activity involves PI3K/Akt inactivation, cAMP elevation, and VASP stimulation that, in turn, suppresses MAPK phosphorylations. This result suggests quercetin may have a potential to treat cardiovascular diseases involving aberrant platelet activation and inflammation.